2013
DOI: 10.4103/0974-9233.120022
|View full text |Cite
|
Sign up to set email alerts
|

Current practice of ophthalmic anesthesia in Nigeria

Abstract: Purpose:To assess the current techniques of ophthalmic anesthesia in Nigeria.Materials and Methods:A cross sectional survey among Nigerian ophthalmology delegates attending the 36th Annual Scientific Congress of the Ophthalmology Society of Nigeria. Self administered and anonymous questionnaires were used and data were collected to include details of the institution, preferred local anesthesia techniques, the grade of doctor who administers the local anesthesia, complications, preferred facial block techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…12 , 13 , 17–19 In Nigeria, peribulbar is the most common anesthesia technique for cataract surgery (49.1%) and retrobulbar is the second most common (37.9%). 20 In our results, retrobulbar anesthesia was the second most common technique used for phacoemulsification (28.3%). In a global survey of cataract practices it was found that topical anesthesia is the preferred technique among participants in more than 90% of routine cases.…”
Section: Discussionmentioning
confidence: 59%
“…12 , 13 , 17–19 In Nigeria, peribulbar is the most common anesthesia technique for cataract surgery (49.1%) and retrobulbar is the second most common (37.9%). 20 In our results, retrobulbar anesthesia was the second most common technique used for phacoemulsification (28.3%). In a global survey of cataract practices it was found that topical anesthesia is the preferred technique among participants in more than 90% of routine cases.…”
Section: Discussionmentioning
confidence: 59%
“…The needle tip state was estimated in a term of Bayesian learning techniques. The distances and angle between the needle tip and sensor are modeled as (14). Thus, the needle tip position and orientation directly affect the state of the sensor array.…”
Section: F Least Squares Estimation (Lsq) With the Maximum Likelihood...mentioning
confidence: 99%
“…As a result, the trainees will not receive feedback if they enter the wrong target area, or damage crucial eye anatomies [11], [12]. Although the complication rate of expert physicians for eye anesthesia is rare (0.1%), the rate of injuries from non-experienced doctors tends to have a significant number around 4% [13], [14]. This issue elucidates the non-effective system for eye anesthesia training.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, it also decreases the intraocular pressure significantly [10] . Adekoya et al [11] reported that currently the most common technique of local anesthesia for an ophthalmic procedure in Nigeria was peribulbar anesthesia, followed by retrobulbar anesthesia. Twelve months prior to the study, 25.9% of the respondents (ophthalmologists) had experienced at least one complication from retrobulbar anesthesia and 16.1% from peribulbar anesthesia.…”
Section: Peribulbar Anaesthesiamentioning
confidence: 99%